2018
DOI: 10.1016/j.cell.2018.03.029
|View full text |Cite
|
Sign up to set email alerts
|

The Evolutionary Landscape of Localized Prostate Cancers Drives Clinical Aggression

Abstract: The majority of newly diagnosed prostate cancers are slow growing, with a long natural life history. Yet a subset can metastasize with lethal consequences. We reconstructed the phylogenies of 293 localized prostate tumors linked to clinical outcome data. Multiple subclones were detected in 59% of patients, and specific subclonal architectures associate with adverse clinicopathological features. Early tumor development is characterized by point mutations and deletions followed by later subclonal amplifications … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

15
220
4
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 202 publications
(240 citation statements)
references
References 51 publications
15
220
4
1
Order By: Relevance
“…A deep sequencing study revealed that a proportion of Gleason grade 3 pattern carcinomas are monoclonal, whereas a subset is composed of multiple subclones. This may imply that the latter are subject to genetic evolutionary changes …”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
“…A deep sequencing study revealed that a proportion of Gleason grade 3 pattern carcinomas are monoclonal, whereas a subset is composed of multiple subclones. This may imply that the latter are subject to genetic evolutionary changes …”
Section: Isup 2014 Grading Of Prostate Cancermentioning
confidence: 99%
“…Numerous recent studies have explored the genomic basis for development of localized prostate cancer, showing distinct evolutionary paths in nonindolent versus indolent disease. The fate of tumors to progress from their somatic progenitors is set early, with alterations in ATM, PTEN, and MYC subclones having predictive power for the existence of higher grade disease including occult oligometastases at the time of radical prostatectomy [9][10][11][12][13]. As the vast majority of these alterations occur as copy number gains or deletions, the percentage of the genome affected by large chromosomal rearrangements is similarly predictive of biochemical recurrence and poor outcome [10,14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Despite being largely regarded as pursuing an indolent clinical course, aggressive behaviors like recurrence or metastasis have been observed and deaths also reported, highlighting the complex and yet poorly understood mechanism [5][6][7][8][9]. There have been extensive reports on the genomic features of common prostate cancer [10][11][12][13][14][15][16][17], and the molecular features of normal human prostate basal cells, prostate basal cell hyperplasia, and basal populations from human prostate cancer have also been reported [18][19][20], but the molecular profile of prostate BCC is still lacking. The mutational and transcriptomic features of this tumor sub-type will thus be valuable for understanding of its tumorigenesis mechanism and development of future clinical treatments.…”
Section: Introductionmentioning
confidence: 99%